Dictionary of commonly cited compounds (London : Chapman & Hall, 2002)
A database containing concise chemical and bibliographic data of 25,000 compounds most commonly used by chemists. Covers organic compouds, inorganic compounds, drugs, natural products, materials, alloys, and the elements and their isotopes.
CD-ROM is available at Makmal Multimedia, Perpustakaan Perubatan.
System requirements: Pentium II Processor or higher; 16MB RAM; 25MB free hard disk space; 24x speed CD-ROM drive or faster; SVGA monitor at 800 x 600, 256 colors; Windows 95, 98, 2000 or NT 4.x.
Keywords: Pharmaceutical Preparations; Biological Factors